Tra persistenza e dissoluzione del personaggio: la questione del déracinement nel romanzo francese contemporaneo (ENTHYMEMA, 2020)
The question of eradication is a relevant issue for the three main interpreters of hypermodern French literature, namely Emmanuel Carrère, Michel Houellebecq and Jonathan Littell. If on the one hand this issue shows its debts to the great season of the 19th- and 20th- century novel, on the other it clearly shows an altogether original articulation, where debts to the realist and modernist traditions coexist with some more recognisably contemporary fiction trends. Once we have analysed the forms taken by this theme, it will be of interest to evaluate not only its effects on the construction of the character, but also its links to the formal organisation of the story.